Experimental field studies with non-human primates - Zuberbühler, Klaus (My University, 2014)
One way to study language evolution is to compare human communication with closely related non-human primate species. This comparative approach has turned to be especially productive if subjects are studied under natural field conditions in which they have evolved. Various observation techniques have been developed, but field experiments are often needed to clarify underlying cause-effect relations. Here, I review the main experimental designs that are suitable for primate fieldwork and discuss some scientific advancements that they have generated. Field experiments are notoriously difficult to carry out for a range of reasons that are discussed. Nonetheless, considerable progress has been made in recent years, including with great apes, which have traditionally been neglected in experimental research in the wild.